PERSEPSI WAJIB PAJAK TERHADAP TAX AMNESTY - Mujiono Mujiono; Suharyono Suharyono (Politeknik Negeri Bengkalis, 2017)
Abstract: In Indonesia, various problems occur such as a high practice of tax avoidance, tax evasion, the morality of taxation, administrative requirements, trust institutions, implementation capacity and lower tax payments. The objective of this study to analyze and obtain empirical evidence, as well as examine whether the experience have significant effect on the name, quality and sacrifice, then to test whether the name, quality and sacrifice have a significant effect on the perception of the taxpayer. The total sample consisted of 100 taxpayers both corporate taxpayers and individual. The results of this study prove that the experience have an impact on the name, quality and sacrifice. But the name, quality and sacrifice have not an impact on the perception of the taxpayer.